VERBAL ABUSE IN MOBILE LEGENDS BANG BANG LIVE STREAMING: A SOCIOLINGUISTIC STUDY - Ni Putu Desi Tresnayanti; I Wayan Swandana; Putu Adi Krisna Juniarta (LINGUA LITERA : journal of english linguistics and literature, 2026)
recorded Mobile Legends: Bang Bang live-streaming sessions on YouTube from a sociolinguistic perspective. The research addresses two main problems: identifying the forms of verbal abuse and examining the motives underlying their use during gameplay interactions. The study applies the sociolinguistic theory of verbal abuse proposed by Blackburn and Kwak (2015) to linguistic behavior in competitive online gaming environments. A qualitative research design was employed using qualitative content analysis. The data were collected from a recorded YouTube live stream by an Indonesian amateur streamer. Observation sheets were used as research instruments to document abusive utterances and explore viewers’ perceptions. The findings revealed four dominant types of verbal abuse: insults and name-calling, blaming and reporting threats, obscene and aggressive language, and threats of in-game sabotage. A total of 54 verbal abuse expressions were identified, with insults and name-calling appearing most frequently. The motives behind verbal abuse included frustration from poor performance, behavioral shifts, emotional disengagement from the team, and the online disinhibition effect.